2022
DOI: 10.1155/2022/6942081
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Core Muscle Strength Training Combined with Taijiquan on Bone Mineral Density Measured by Quantitative CT Scanning in the Elderly

Abstract: Learn about the benefits of muscle strength training combined with tai chi for adult skeletal muscle in multiple CT scanning. The study included 182 people over the age of 60 with no long-term history of physical activity and exercise. They were divided into the Taijiquan group (52 people), student muscle strength group (45 people), student muscle group combined with Taijiquan group (45 people), and control group (40 people). The board of directors did not attend. The other three groups received tai chi (more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…In contrast to previous research, Wayne et al employed the Wilcoxon rank-sum test, setting their study apart [ 30 ]. Recent investigations on the effects of various TC exercise programs on BMD in middle-aged and older adults [ 21 , 31 , 32 ] have predominantly utilized ANOVA. This approach has gained traction because a single comparison between two groups may not adequately represent the positive impact of diverse TC programs on BMD, given substantial variations in intensity, frequency, and duration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to previous research, Wayne et al employed the Wilcoxon rank-sum test, setting their study apart [ 30 ]. Recent investigations on the effects of various TC exercise programs on BMD in middle-aged and older adults [ 21 , 31 , 32 ] have predominantly utilized ANOVA. This approach has gained traction because a single comparison between two groups may not adequately represent the positive impact of diverse TC programs on BMD, given substantial variations in intensity, frequency, and duration.…”
Section: Discussionmentioning
confidence: 99%
“…This dysfunction subsequently causes alterations in bone morphology, including changes in DNA and collagen synthesis, which contribute to a decline in BMD. While exercise alone cannot fully counteract the reduction in bone mineral content, it has notable effects on bone blood circulation and can mitigate bone mineral loss, actively foster bone cell formation, and thus play a crucial role in the prevention of OP [ 31 ]. Moderate exercise is known to significantly elevate overall BMD, modulate bone metabolism, and moderately increase BMD throughout the body.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%